2013
DOI: 10.1039/c3cs60223k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the chemoselective reduction of functional groups mediated by samarium(ii) iodide: a single electron transfer approach

Abstract: Recently, samarium(II) iodide reductants have emerged as powerful single electron donors for the highly chemoselective reduction of common functional groups. Complete control of the product formation can be achieved on the basis of a judicious choice of a Sm(II) complex/proton donor couple, even in the presence of extremely sensitive functionalities (iodides, aldehydes). In most cases, the reductions are governed by thermodynamic control of the first electron transfer, which opens up new prospects for unpreced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(113 citation statements)
references
References 274 publications
6
107
0
Order By: Relevance
“…However, treatment of 36 with bulky Superhydride resulted in the exclusive formation of 5‐ epi ‐huperzine Q ( 37 ) by hydride attack from the convex face. Finally, 36 was converted into (−)‐huperzine Q ( 1 ) quantitatively by using SmI 2 in the presence of H 2 O, presumably owing to the initial formation of the axial radical followed by protonation to afford the equatorial alcohol . The spectroscopic data of synthetic (−)‐huperzine Q fully matched the reported data …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, treatment of 36 with bulky Superhydride resulted in the exclusive formation of 5‐ epi ‐huperzine Q ( 37 ) by hydride attack from the convex face. Finally, 36 was converted into (−)‐huperzine Q ( 1 ) quantitatively by using SmI 2 in the presence of H 2 O, presumably owing to the initial formation of the axial radical followed by protonation to afford the equatorial alcohol . The spectroscopic data of synthetic (−)‐huperzine Q fully matched the reported data …”
Section: Resultssupporting
confidence: 71%
“…Finally, 36 was converted into (À)-huperzine Q( 1)q uantitativelyb yu sing SmI 2 in the presence of H 2 O, presumably owing to the initial formation of the axial radical followed by protonation to afford the equatorial alcohol. [23] The spectroscopic data of synthetic (À)-huperzineQfully matched the reported data. [3] As aforementioned, cyclization product 36 could be obtained in 43 %y ield along with enamine 5 in a1 :1 ratio from alcohol 33.T he same mixture of 5 and 36 (1:1.2) waso btained upon treating either enamine 5 or 36 with (+ +)-CSA at 160 8C for 30 min (Table 2), which indicated that 5 existed in equilibrium with 36 under the acidic conditions presumably via iminium ion intermediate 35.…”
Section: Retrosynthetic Analysissupporting
confidence: 67%
“…1 Additives are commonly used to increase the effectiveness and versatility of SmI 2 . These are Lewis bases which make SmI 2 more reducing and often provide protons, such as methanol and water.…”
Section: Introductionmentioning
confidence: 99%
“…Redox behaviour of trivalent lanthanide ions is expected to be quite interesting, especially of Eu, Yb and Sm, having electronic configuration approaching or attending half filled or full filled 4f orbitals. [19][20][21][22][23][24][25][26][27][28][29] In fact, limited studies have been carried out on the ET processes involving divalent lanthanide ions as the electron donors. [15][16][17][18] The one electron reduction potential of Eu(III) is most favourable in the Table 1 Electronic configurations of trivalent lanthanide ions along with their one-electron reduction potentials [15][16][17][18] series due to the formation of a half-filled f-subshell in Eu(II) stabilizing the product state.…”
Section: Introductionmentioning
confidence: 99%
“…One-electron reduction potentials of trivalent lanthanide ions E Ln(III)/Ln(II) are listed in Table 1. [23][24][25][26][27][28][29] For, trivalent lanthanide ions, even though their reduction potentials are not very favorable, yet they can participate in a photoinduced electron transfer (PET) reaction, as the excitation energy adds favourably towards the energetics of the ET process. Similarly the one electron reduction potential of Yb(III) is favourable due to the formation of a completely filled f-subshell in Yb(II).…”
Section: Introductionmentioning
confidence: 99%